Reconciling household surveys and national accounts data using a cross entropy estimation method - Robilliard, Anne-Sophie; Robinson, Sherman (Wiley, 2003)
This paper presents an approach to reconciling household surveys and national accounts data. The problem is how to use the information provided by the national accounts data to re‐estimate the household weights used in the survey so that the survey results are consistent with the aggregate data. The estimation approach uses an estimation criterion based on an entropy measure of information. The survey household weights are treated as a prior. New weights are estimated that are close to the prior and that are also consistent with the additional information. This approach is implemented to reconcile household survey data and macro data for Madagascar. The results indicate that the approach is powerful and flexible, supporting the efficient use of information from a variety of sources to reconcile data at different levels of aggregation in a consistent framework.